2017
DOI: 10.1261/rna.063172.117
|View full text |Cite
|
Sign up to set email alerts
|

CeFra-seq reveals broad asymmetric mRNA and noncoding RNA distribution profiles in Drosophila and human cells

Abstract: Cells are highly asymmetrical, a feature that relies on the sorting of molecular constituents, including proteins, lipids, and nucleic acids, to distinct subcellular locales. The localization of RNA molecules is an important layer of gene regulation required to modulate localized cellular activities, although its global prevalence remains unclear. We combine biochemical cell fractionation with RNA-sequencing (CeFra-seq) analysis to assess the prevalence and conservation of RNA asymmetric distribution on a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 78 publications
(103 reference statements)
7
88
0
Order By: Relevance
“…This type of analysis can thus be useful in identifying molecular machines that are likely enriched at specific subcellular compartments through localized translation. Finally, similar to mRNA profiling efforts, these types of subcellular transcriptomics studies have also revealed the extensive asymmetry in distribution patterns displayed by various families of noncoding RNAs, including lncRNAs, miRNAs, and circular RNAs . Collectively, these approaches highlight that high prevalence and diversity of RNA localization events.…”
Section: Biological Functions and Prevalence Of Rna Localizationmentioning
confidence: 83%
See 3 more Smart Citations
“…This type of analysis can thus be useful in identifying molecular machines that are likely enriched at specific subcellular compartments through localized translation. Finally, similar to mRNA profiling efforts, these types of subcellular transcriptomics studies have also revealed the extensive asymmetry in distribution patterns displayed by various families of noncoding RNAs, including lncRNAs, miRNAs, and circular RNAs . Collectively, these approaches highlight that high prevalence and diversity of RNA localization events.…”
Section: Biological Functions and Prevalence Of Rna Localizationmentioning
confidence: 83%
“…Using a combined approach of RNA‐seq and MS profiling of human and Drosophila cells fractionated into distinct biochemically defined compartments (i.e., nuclear, insoluble, endomembrane, and cytosol), Benoit Bouvrette et al . found that the majority of mRNAs and noncoding RNA biotypes are asymmetrically distributed in patterns that are generally conserved evolutionarily . Comparative analysis of mRNA and protein distribution profiles revealed a general lack of correlation, a feature that was strongly influenced by specific families of transcripts exhibiting strong asymmetric distribution with their encoded protein products.…”
Section: Biological Functions and Prevalence Of Rna Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now clear that rather than being uniformly distributed throughout the cytoplasm, the 50 majority of eukaryotic mRNAs exhibit specific subcellular localizations (Benoit Bouvrette et al, 2018;Lecuyer et al, 2007;Wang et al, 2012;Wilk et al, 2016). Such localization can act as a means of localizing the encoded proteins (Zappulo et al, 2017), or function instead as a mechanism for post-transcriptional regulation by modulating the access of mRNAs to different trans-acting factors (Kejiou and Palazzo, 2017;Pizzinga et al, 2019;Prasanth et al, 55 2005).…”
Section: Introductionmentioning
confidence: 99%